Strategi Mewujudkan Kesejahteraan Sosial melalui Lembaga Keuangan Mikro Syariah - Fatmawati Sungkawaningrum (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2018)
This article discusses the strategy of realizing prosperity in the community, so that every community has a business and can be lifted from poverty. The method of writing this article uses descriptive analysis, which explains the strategy to realize social welfare through Islamic microfinance institutions. From the results of the discussion that Islamic microfinance institutions could be an alternative to overcome poverty in Indonesia. That is because many poor people in Indonesia are not accessed by formal banking. Microfinance institutions can facilitate providing loans, with easier conditions, encourage people to have business products, conduct training and program socialization that are both direct and indirect.The government's duty is to eradicate unfair economic policies, uneven distribution of assets, sanction corruptors. The government has issued various regulations for poverty alleviation. The alleviation of poverty and empowerment of the people who live mostly through MSMEs (micro, small and medium enterprises) has been hit with a fundamental problem, namely bank procedures that must be obeyed. Because banks must carry out the principle of prudence in releasing credit to customers. MSMEs, which are generally not in accordance with bank standards, have difficulties in obtaining access to credit. Then a pattern must be built. Alternative microfinance institutions that can be offered are the BMT (Baitul mall wa Tamwil) and savings and loan cooperatives. With the hope that a prosperous society can be realized.